Standard codecs image compression to advanced video coding - Ghanbari, M. (Mohammed) (The Institution of Engineering and Technology, 2011)
The following topics are dealt with: content-based advanced video coding; video compression; subband coding; wavelet transform; JPEG2000; JPEG; videoconferencing; H.261; digital storage media; MPEG-1; high-quality moving pictures; MPEG-2; bit rate communication; H.263; MPEG-4 visual; H.264; MPEG-7 and MPEG-21.